Hygienic Quality of Air-Packed and Refrigerated or Frozen Stored Döner Kebab and Evaluation of the Growth of Intentionally Inoculated Listeria monocytogenes - Francesca Coppola; Giada Ferluga; Lucilla Iacumin; Cristian Bernardi; Michela Pellegrini; Giuseppe Comi (Microorganisms)
Döner kebab, a meat product of Middle-Eastern origin, has gained significant popularity and is now widely consumed across Europe. The recipe varies depending on the area, with beef, turkey, lamb, or chicken being used as main ingredients. The aim of this work was to assess the hygienic-sanitary quality of raw and cooked döner kebabs stored at 4 ± 2 °C for 10 days and at 8 ± 2 °C for the next 20 days or frozen (−18 °C) for one month. One additional aim was to determine the potential growth of Listeria monocytogenes intentionally inoculated in cooked döner kebab during storage at 4 ± 2 °C or freezing. The concentration of Total Viable Count (TVC) and the Enterobacteriaceae of the 100 samples of raw döner kebab were less than 7 log CFU/g and 4 log CFU/g, respectively. Consequently, the samples can be considered acceptable and similar to traditional raw meat. The cooked döner kebab can be considered safe for a period of 30 days, especially from a microbiological point of view, when stored under refrigerated conditions, also taking into account possible thermal abuse. Coagulase Positive Cocci (CPC), Clostridium H2S+, Salmonella spp., and Listeria monocytogenes were never found in any of the samples. After 30 days, the TVC was at the level of 6 log CFU/g and Enterobacteriaceae at less than 4 log CFU/g. The main concern was related to microbial or tissue activity, resulting in an increase in total volatile basic nitrogen (TVB-N) content. However, in the cooked samples, the TVB-N content remained below 40 mg N/100 g at the end of the shelf-life period (32.5 mg N/100 g), which is still considered an acceptable value. In addition, the level of Malondialdehyde (MDA) was found to be within acceptable limits, with a reading of 1.4 nmol/g attained after 30 days. The same product, when frozen and stored at −18 °C, can be considered stable for a minimum of 6 months, both from a microbiological and a physico-chemical point of view. No microbial growth was observed. The TVB-N and the MDA levels increased, but after 6 months, their levels were still acceptable, with values of 19.1 mg N/100 g and 1.2 nmol/g, respectively. These observations demonstrate low protein degradation and lipid oxidation during the shelf-life period. The challenge test showed that Listeria monocytogenes did not grow in döner kebab either when stored at 4 ± 2 °C for 10 days and 8 ± 2 °C for 20 days or when stored at −18 °C for 6 months. The concentration of L. monocytogenes was found to be 5.4 log CFU/g in the refrigerated products and 4.9 log CFU/g in the frozen products. At the end of the shelf-life period, the L. monocytogenes load in both products was lower than the initial concentration that had been added. Finally, the use of air-packaging has been proven to be beneficial to the preservation of the product and maintained its microbiological and physico-chemical properties intact. Despite these good results, future directions could be to investigate different plastic films and packaging such as Modified Atmosphere (MAP), Vacuum (VP), and Sous Vide packaging (SVP).